Aspergillus fumigatus and personalized medicine: Toward a clinically reliable algorithm - Caminati, Marco; Feleszko, Wojciech; Michel, Moïse; Annesi‐Maesano, Isabella; Vitte, Joana (Allergy (Copenhagen), 2022)
We read with interest the contribution by Lukaszewicz et al providing an overview of the diagnostic criteria for allergic broncho-pulmonary aspergillosis (ABPA) and mycosis (ABPM) and elaborating on the need for expanding the use of molecular allergen approach in the assessment of genuine allergic sensitization versus cross-reactivity to Aspergillus fumigatus ( Af). The proposed algorithm acknowledges recent progress; however, it overlooks controversial issues in ABPA diagnostics reliability and does not assist with early recognition of ABPA among subsets of allergic fungal airway disease and overlapping conditions, an important step in proper patient management and treatment selection. [...]